Evolving the practitioner–teacher role to enhance practice–academic partnerships: a literature review. Issue 5 (29th October 2015) - Kleinpell, Ruth M; Faut‐Callahan, Margaret; Carlson, Elizabeth; Llewellyn, Jane; Dreher, Melanie
Abstract : Aims and objectives: The purpose of this article was to review the development of the practitioner–teacher model and its use in advancing clinical nursing. Background: The practitioner–teacher role, or the unification model, incorporates clinical practice, teaching, consultation and research responsibilities for nurses serving in advanced clinical roles or as nursing faculty as part of professional nursing practice. The practitioner–teacher role facilitates a practice–academic partnership that can serve as a beneficial way to advance clinical nursing care. Design: An exploratory literature review was conducted combined with review of practitioner–teacher and practice–academic exemplars. Methods: A descriptive review of the practitioner–teacher model of nursing practice reveals that activities of the role include clinical nursing care, serving as a preceptor for nursing students in a focused area of expertise, consulting on patient care issues, presenting in‐services and course lectures, and serving as a member of faculty and nursing division committees. Results: The practitioner–teacher role lends itself to promoting practice–academic partnerships that combine clinical nursing care with professional nursing activities. Conclusions: The model of practice, education, consultation and research of the practitioner–teacher position advances practice–academic partnerships. Relevance to clinical practice: The practitioner–teacher model serves to optimise the way nursing practice and academic work together to integrate knowledge, scholarship, service and learning and to advance the profession and the discipline of nursing. This article discusses aspects of the unique practice–academic partnership using the practitioner–teacher model, how the role evolved, and how it can improve clinical nursing care globally.